Analysis of Spare Parts Inventory Planning for Machinery with Monte Carlo Simulation, Reorder Point, and Safety Stock - Farisan, Fahreza; Purba, Arini Anestesia; Arham Pratikno, Faishal (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
PT. XYZ is a company engaged in the management of mall buildings. The implementation of operations in malls often experiences obstacles, namely the availability of machine spare parts which is less than 95% of the standard inventory availability. The impact of this problem is the ability of PT. XYZ in meeting the needs of consumers. The results of observations and interviews with supervisors show that there is a lack of stock of escalator spare parts, especially for Sigma brands such as Ballasstrude Newel Chain Roller Escalator Sigma Vera, Roller Press Handrail (70x60) Sigma Ares, Roller Press Handrail Escalator Sigma Vera and Roller Step ESC Sigma (6204). This study compares three forecasting methods: exponential smoothing, linear regression, and Monte Carlo simulation. The stages of the research consist of problem identification, determination of data patterns, inventory planning with montecarlo simulations, raw material planning with safety stock and reorder points. The results of this study were obtained that the best method to handle this case was Monte Carlo simulation because it has a high level of accuracy compared to other methods. The accuracy result obtained was a Mean Absolute Percentage Error (MAPE) of 17.03%. The results of the Montecarlo simulation obtained safety stock of 9-16 units and reorder points of 18-28 units. This research can reduce delays in fulfilling production demand, if safety stock and reorder point policies can be implemented.